Estudo das propriedades mecânicas em embalagens de papel à base de poliacrilamida e fibras naturais - Ferreira dos Santos, Danielle; Vasconcelos, A J (Revista Interdisciplinar de Pesquisa em Engenharia, 2022)
Natural fibers have been extensively studied as a reinforcement filler in obtaining composites, replacing partially synthetic fibers. The vast majority of these materials originate from agro-industrial waste with a high content of lignin and cellulose making it a very interesting material with low cost and good mechanical properties. The purpose of the study was to obtain a composite based on alkyl ketene dimer resin, for the manufacture of sustainable packaging, made of paper by adding a 10% (w/w) con-tent of green coconut fiber and sugarcane bagasse fiber, and evaluated the impact of the filler on the mechanical behavior of the systems. The studied material was characterized from mechanical tests, such as Ring Crush Test (RCT) and Concora Medium Test (CMT) evaluating the maximum resistance supported by centimeter in the pre-pared composites, through the specimens. It was observed that the composite prepared with the sugarcane bagasse fiber presented the most satisfactory results, thus converging on the material with better mechanical properties, when compared to the compo-site obtained with green coconut fiber. Therefore, the study was funneled with sugar cane fiber, varying the content by 20 and 30 % (w/w), evaluating the impact on the dispersion of this filler in the polymeric matrix and, consequently, the mechanical response of the composite with these compositions.